PARALLEL ANALYSIS OF KABAALA IYA AZHAL IN SIDDHA LITERATURE WITH SINUSITIS - Saranya, R. (International Journal of Ayurveda and Pharma Research, 2017)
Siddha system is one of the primordial health sciences with historical, anthropological, archeological and geographical evidences. The medical philosophies of Siddha were presented in poetic forms in palm scripts which cannot be easily interpreted by common man. According to this system, the disease classification is based on the concepts of Tridosha pathology (Vatham, Pitham and Kabham) that seems poles apart from those of the International Classification of Diseases (ICD) when viewed afar. This review article is an attempt to correlate clinically, the symptoms of â€œKabaala Iya Azhalâ€, a disease given in the Siddha text Pararasasegaram with that of the common ailment Sinusitis mentioned in contemporary science. Through meticulous interpretation and parallel analysis of the condition it can be concluded that even the mediocre signs and symptoms of Kabaala Iya Azhal can be correlated well with that of Sinusitis. This parallel analysis would further pave way for better perceptive, diagnosis and management of the disease â€œKabaala Iyya Azhalâ€ as mentioned in Siddha literature.